Peranan Pengajar Mata Pelajaran Agama dalam Membentuk Sikap Keagamaan Siswa di SMP Negeri 1 Tanjung Raya - Davinta Zulkarnaen; Saras Rama Dani; Melvi Indy Anggawati (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2024)
This research discusses the important role of teaching religious subjects in shaping students' religious attitudes at SMP Negeri 1 Tanjung Raya. Religion teachers have a big responsibility in developing students' religious understanding, appreciation and practice. This research uses a qualitative approach with data collection techniques through observation and structured interviews with religious teachers and students. The research results show that the role of religious teachers is very influential in shaping students' religious attitudes, with a focus on learning moral and spiritual values ​​in the context of Islamic education at school.